Monocyte/HDL Cholesterol Ratios as a New Inflammatory Marker in Patients with Schizophrenia - Kilic, Nueluefer; Tasci, Gulay; Yilmaz, Seda; Oner, Pinar; Korkmaz, Sevda (Mdpi, 2023)
Purpose: Monocyte/HDL cholesterol ratio (MHR) is a novel inflammatory marker that is used as a prognostic factor for cardiovascular diseases and has been studied in many diseases. The aim of this study was to investigate the role of inflammatory factors in schizophrenia patients by examining MHR levels and to compare schizophrenia patients and healthy controls in terms of cardiovascular disease risk. Method: A total of 135 participants between the ages of 18-65, 85 diagnosed with schizophrenia, and 50 healthy individuals in the control group were included in this cross-sectional study. Venous blood samples were taken from the participants and CBC parameters and lipid profiles were analyzed. The sociodemographic and clinical data form and positive and negative symptoms scale (PANSS) were administered to all participants. Results: Although monocyte levels were significantly higher in the patient group, HDL-C levels were lower at significant levels. MHR was found to be higher in the patient group compared to the control group at significant levels. When compared to the control group, total cholesterol, triglyceride, WBC, neutrophil, basophil, and platelet levels were higher in the patient group at significant levels, and RBC, hemoglobin, and hematocrit levels were significantly lower. Conclusion: The elevated MHR in patients with schizophrenia may contribute to our understanding that inflammation plays important roles in the pathophysiology of schizophrenia. Additionally, knowing the levels of MHR and considering the recommendations, such as diet and exercise, in the treatment approaches made us think that it might be beneficial in protecting schizophrenia patients against cardiovascular diseases and early death.
Keywords: schizophrenia; monocytes; HDL-C; MHR; inflammation